2021
DOI: 10.3390/ijerph182212142
|View full text |Cite
|
Sign up to set email alerts
|

Activated Carbon from Palm Date Seeds for CO2 Capture

Abstract: The process of carbon dioxide capture and storage is seen as a critical strategy to mitigate the so-called greenhouse effect and the planetary climate changes associated with it. In this study, we investigated the CO2 adsorption capacity of various microporous carbon materials originating from palm date seeds (PDS) using green chemistry synthesis. The PDS was used as a precursor for the hydrochar and activated carbon (AC). Typically, by using the hydrothermal carbonization (HTC) process, we obtained a powder t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The activated carbons prepared from hydrochar from the PPS waste had a relatively low surface area. However, they were still higher than those in some related recent studies, as for example activated carbons from Nauclea diderrichi [68] and date palm seeds [69]. Activated carbons such as those in this study are relevant to many applications [70][71][72].…”
Section: Adsorption/desorption Of N 2 and Comentioning
confidence: 47%
“…The activated carbons prepared from hydrochar from the PPS waste had a relatively low surface area. However, they were still higher than those in some related recent studies, as for example activated carbons from Nauclea diderrichi [68] and date palm seeds [69]. Activated carbons such as those in this study are relevant to many applications [70][71][72].…”
Section: Adsorption/desorption Of N 2 and Comentioning
confidence: 47%
“…The seeds were subsequently removed and ground into powder after being carbonized for 120 minutes at 400 °C in the furnace. The powder was then added to the sodium hydroxide solution for activation [38]. The activated carbon was placed in a furnace set at 700 degrees Celsius for two hours.…”
Section: Preparation Of Activated Carbon From Date Palm Seedsmentioning
confidence: 99%
“…Banana occupies the fourth world rank of the most significant foodstuffs [16]. On the other hand, Saudi Arabia has more than 23 million specimens of palm trees [30]. It was reported that KSA palm date fruit production reached about 1,078,300 metric tons in 2010, which represents 14.4% of the world's production [31].…”
Section: Cytotoxicity Assaymentioning
confidence: 99%